Strategi Pemasaran Usaha Mikro Kecil Menengah Untuk Meningkatkan Pendapatan Masyarakat Kajian Hukum Ekonomi Syariah (Studi di Desa Wanajaya Kecamatan Wanaraja Kabupaten Garut) - Sulthonuddin, Bung Hijaj; Candrasya, Rizki Fauzan (Jurnal Hukum Ekonomi Syariah, 2024)
Analysis of markets, customers and products is very important in the business world. Strategy analysis includes the "Strategy Triangle", namely: Customers, Competitors and Companies. Most companies/business units carry out production and operational activities only to concentrate on making products, including small to medium scale companies. Companies should also pay attention to business strategies to maintain the development of existing businesses, so that they can remain competitive. The formulation of the problem in this research is: How is the Community MSME Strategy Planning in Wanajaya Village to Improve the Community's Economy? and What is the Marketing Strategy for UMKM to Increase Community Income? Study of Sharia Economic Law in Wanajaya Village? So this research aims to determine the condition of UMKM in Wanajaya Village, Wanaraja District, Garut Regency. This research is included in the type of qualitative research by approaching it using interview techniques, literature and documentation. The data was analyzed through the stages of data reduction, data presentation, then drawing conclusions. Based on the results of this research, UMKM in their planning understand the product so that it is free from haram elements but are constrained by capital problems and also the use of technology, but in terms of people's income, of course the community is greatly helped by the existence of these UMKM.  Keywords: Marketing Strategis, Community Income, Sharia Economic Law.